2012
DOI: 10.1179/1077352512z.00000000034
|View full text |Cite
|
Sign up to set email alerts
|

Toxicology of food dyes

Abstract: This review finds that all of the nine currently US-approved dyes raise health concerns of varying degrees. Red 3 causes cancer in animals, and there is evidence that several other dyes also are carcinogenic. Three dyes (Red 40, Yellow 5, and Yellow 6) have been found to be contaminated with benzidine or other carcinogens. At least four dyes (Blue 1, Red 40, Yellow 5, and Yellow 6) cause hypersensitivity reactions. Numerous microbiological and rodent studies of Yellow 5 were positive for genotoxicity. Toxici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
107
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(116 citation statements)
references
References 72 publications
0
107
0
Order By: Relevance
“…(108) Coal-tar dyes are considered carcinogenic for humans. (109) Sodium hydroxide Sodium hydroxide is an inorganic compound, also known as caustic soda or lye. As per the codex alimentarius commission, sodium hydroxide can be used in fermented milks and other dairy products as per the provisions of GMP, but is not allowed in raw milk.…”
Section: Downloaded By [Selcuk Universitesi] At 05:28 03 February 2015mentioning
confidence: 99%
“…(108) Coal-tar dyes are considered carcinogenic for humans. (109) Sodium hydroxide Sodium hydroxide is an inorganic compound, also known as caustic soda or lye. As per the codex alimentarius commission, sodium hydroxide can be used in fermented milks and other dairy products as per the provisions of GMP, but is not allowed in raw milk.…”
Section: Downloaded By [Selcuk Universitesi] At 05:28 03 February 2015mentioning
confidence: 99%
“…Toxicological studies have shown that dyes do not harm health if used within the limits defined by legislation. Nevertheless, there is still controversy about their possible harm, especially given the exaggerated consumption of industrialised products that currently occurs, particularly by children …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there is still controversy about their possible harm, especially given the exaggerated consumption of industrialised products that currently occurs, particularly by children. 2 In humans, consumption of a balanced diet rich in carotenoids has been inversely associated with the risk of diseases such as cancer 3 and macular degeneration. 4 In addition, some results describe a relationship between retinal carotenoids and neuroelectric indices underlying cognitive control 5 indicating that regular consumption of carotenoids is associated with maintaining health and wellness.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous microbiological and rodent studies of Yellow (5) were positive for genotoxicity. Toxicity tests performed on two dyes; Citrus Red (2) and Orange B also suggest safety concerns, but Citrus Red (2) is used at low levels and only in some Florida oranges and Orange B has not been used for several years [70]. All dog food contains derivatives from all types of meat, and viscera, such as the liver, are a=Only case where dry food was more contaminated with AFL than canned food, there was more biotransformation of basic aflatoxins to the AFL hydroxylate metabolite.…”
Section: Samplingmentioning
confidence: 99%
“…Among the AF risk ingredients of dog food are cereals, such as corn and rice, and leguminosae, such as soybean, which are frequently contaminated with AFs. Artificial pigments pose a cancer risk [70]. Red (40), Yellow (5), and Yellow (6) have been found to be contaminated with benzidine or other carcinogens.…”
Section: Samplingmentioning
confidence: 99%